2004
DOI: 10.1161/01.cir.0000142615.88444.31
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role for Heat Shock Protein 72 in Antagonizing Cerebral Vasospasm After Rat Subarachnoid Hemorrhage

Abstract: Background-Cerebral vasospasm can be defined as delayed-onset narrowing of the cerebral arteries that can occur after a spontaneous aneurysmal subarachnoid hemorrhage (SAH). Despite a large number of experimental and clinical investigations, the exact pathophysiology of vasospasm remains unknown. Using a fluorescence differential-display system, we have identified the gene encoding heat shock protein 72 (HSP72) as being highly upregulated by cerebral vasospasm. We therefore elucidated the role of the HSP72 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
(32 reference statements)
2
28
0
Order By: Relevance
“…Furthermore, the antisense ODNs used in the present study were phosphorothioated to prevent their degradation by endogenous enzymes (Putney et al, 1981). The dose regimen of the antisense ODNs was based on reported studies (Satoh et al, 2002;Nikaido et al, 2004). We report a substantial (Ͼ80%) reduction in nischarin level in the RVLM of rats treated with nischarin antisense ODN.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the antisense ODNs used in the present study were phosphorothioated to prevent their degradation by endogenous enzymes (Putney et al, 1981). The dose regimen of the antisense ODNs was based on reported studies (Satoh et al, 2002;Nikaido et al, 2004). We report a substantial (Ͼ80%) reduction in nischarin level in the RVLM of rats treated with nischarin antisense ODN.…”
Section: Discussionmentioning
confidence: 91%
“…Although rat models of SAH have been used widely to study the impact of subarachnoid blood on the brain and cerebral vasculature (37,46), caution should be used in extrapolating data obtained from rodents to SAH-induced pathologies observed in humans after cerebral aneurysm rupture. For example, pial artery vasospasm in SAH model rats is less severe and of shorter time course than reported in canine and primate SAH models or in many cases of SAH-induced vasospasm in humans (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that HSP72 can protect a variety of cells, including renal tubule cells, from thermal, toxic, and ATP depletion-mediated injury in vitro (31,35,47). Enhanced HSP72 expression also ameliorates myocardial, liver, brain, and renal damage induced by ischemia-reperfusion, cyclosporin, and endotoxin exposure in rats (9,10,26,35). Our preliminary results (data not shown), as well as those reported by others, showed that after ureteric obstruction, increased HSP72 expression started at day 3, peaked at day 7, and was maintained over the following 14 days, which paralleled the progression of renal fibrosis (18,37).…”
Section: Discussionmentioning
confidence: 99%